ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTS (HSCT) WITH ADAPTED FLAMSA CAN CURE HALF OF THE PEDIATRIC PATIENTS WITH REFRACTORY ACUTE MYELOGENOUS LEUKEMIA (AML) - ACR Correa; AF Martins; ACR Donatelli; CN Santos; MF Cardoso; LL Quintino; G Zamperlini; LDS Domingues; AVL Sousa; A Seber (Hematology, Transfusion and Cell Therapy, 2023)
Introduction: AML represents 20% of the pediatric acute leukemias and 40% of the patients succumb to refractory disease, relapse, or treatment-related toxicities. Patients with refractory disease have the worst outcomes and are usually referred to exclusive palliative care. HSCT in patients with active AML is controversial, but the FLAMSA regimen, a sequential cytoreduction followed by allogeneic HSCT, initially developed to treat adult patients, has been used by the BFM group with very promising results. This strategy was suggested by the Brazilian GELMAI group, but results are still unknown. O Objective: To evaluate the outcome of allogeneic HSCT in patients with refractory AML. Method: Retrospective study of all pediatric patients undergoing HSCT for the treatment of refractory AML in a single center. Refractoriness was considered the presence of more than 5% blasts on morphology, confirmed by flow cytometry in the majority of patients. Three conditioning regimens were used: Busulfan, Fludarabine and Melphalan (Bu-Flu-Mel; Jaiswal et al.), Total Body Irradiation (TBI) and fludarabine (Solomon et al.), and adapted FLAMSA ‒ Fludarabine, Etoposide and Cytarabine followed by Busulfan (Bu)-based conditioning, associated to Fludarabine (Flu) or Cyclophosphamide (Cy) and Melphalan (Mel) according to the patients’ clinical conditions. Results: A total of 89 transplants were performed between 2017 and 2023 for pediatric AML. Of these, 15 transplants in 13 patients were performed for refractory AML (two second HSCT were for relapse and graft failure, one each). The median age was 8.2 years and 54% of the patients were male. In 40% of the patients, AML was FAB-M4 (FAB), followed by M1 (20%) and M7 (20%). Donors were 80% haploidentical (haplo), 13% Unrelated (MUD) and 7% a Matched Sibling (MSD). The graft was bone marrow in 9 (60%) and in 40%, peripheral blood. All 15 HSCT used a myeloablative regimen (MAC): 4 (27%) Bu-Flu-Mel, 2 (13%) Flu-TBI and 8 (53%) adapted FLAMSA. GVHD prophylaxis used PT-Cy, Calcineurin Inhibitor (CI) – MMF in Haplos, CI and Methotrexate in MUD and CI in MSD. Only 4 patients received DLI, but 8 of 13 patients (62%) developed acute or chronic Graft-Versus-Host Disease (GVHD). Eight of 13 patients died of relapse (4), infection (3) or alveolar hemorrhage (1). Of the 6 patients receiving Bu-Flu-Mel of Flu-TBI, only 1 remains alive in remission. Of the 8 patients who underwent adapted FLAMSA, 2 died of relapse, 2 died of infection and 4 remain alive and disease free a median of 4.4 months (75–377 days) after the HSCT. Conclusion: The adapted FLAMSA regimen may cytoreduce the tumor burden with a low toxicity prior to HSCT, demonstrating that it may be possible to improve survival of patients with refractory/relapsed AML.